Athelium imperceptum Nyl. (Thelocarpaceae, Ascomycota), a scarcely known ephemeral lichen of biological soil crusts, new to Ukraine (CHORNOMORSKI BOTANICAL JOURNAL, 2011)
Our new record to Ukraine of a rare lichen Athelium imperceptum (syn. Thelocarpon imperceptum) is discussed. We provide data on ecology of the species and its European distribution and we have also made up modern diagnoses of both, the genus Athelium and the species A. imperceptum. The recovered genus Athelium is distinguished from Thelocarpon by the absence of pulvinic acid derivates forming a superficial yellow pruina on perithecia; its perithecia rather resemble those of Thelopsis rubella. Thelocarpon magnussonii is also devoid of yellow pruina (probably a secondary lost) but it differs from A. imperceptum by its well-developed thalline exciple.
Keywords: Athelium imperceptum, Kelleria polyspora, biological soil crust, Thelopsis, Thelocarpon, Ukraine.